Identification of Polycystic Kidney Disease 1 Like 1 Gene Variants in Children With Biliary Atresia Splenic Malformation Syndrome. Issue 3 (21st March 2019) - Berauer, John‐Paul; Mezina, Anya I.; Okou, David T.; Sabo, Aniko; Muzny, Donna M.; Gibbs, Richard A.; Hegde, Madhuri R.; Chopra, Pankaj; Cutler, David J.; Perlmutter, David H.; Bull, Laura N.; Thompson, Richard J.; et al.
Abstract : Biliary atresia (BA) is the most common cause of end‐stage liver disease in children and the primary indication for pediatric liver transplantation, yet underlying etiologies remain unknown. Approximately 10% of infants affected by BA exhibit various laterality defects (heterotaxy) including splenic abnormalities and complex cardiac malformations—a distinctive subgroup commonly referred to as the biliary atresia splenic malformation (BASM) syndrome. We hypothesized that genetic factors linking laterality features with the etiopathogenesis of BA in BASM patients could be identified through whole‐exome sequencing (WES) of an affected cohort. DNA specimens from 67 BASM subjects, including 58 patient–parent trios, from the National Institute of Diabetes and Digestive and Kidney Diseases–supported Childhood Liver Disease Research Network (ChiLDReN) underwent WES. Candidate gene variants derived from a prespecified set of 2, 016 genes associated with ciliary dysgenesis and/or dysfunction or cholestasis were prioritized according to pathogenicity, population frequency, and mode of inheritance. Five BASM subjects harbored rare and potentially deleterious biallelic variants in polycystic kidney disease 1 like 1 ( PKD1L1 ), a gene associated with ciliary calcium signaling and embryonic laterality determination in fish, mice, and humans. Heterozygous PKD1L1 variants were found in 3 additional subjects. Immunohistochemical analysis of liver from the one BASM subject available revealed decreased PKD1L1 expression in bile duct epithelium when compared to normal livers and livers affected by other noncholestatic diseases. Conclusion: WES identified biallelic and heterozygous PKD1L1 variants of interest in 8 BASM subjects from the ChiLDReN data set; the dual roles for PKD1L1 in laterality determination and ciliary function suggest that PKD1L1 is a biologically plausible, cholangiocyte‐expressed candidate gene for the BASM syndrome.